1994
DOI: 10.1104/pp.105.3.981
|View full text |Cite
|
Sign up to set email alerts
|

Proline Accumulation in Maize (Zea mays L.) Primary Roots at Low Water Potentials (I. Requirement for Increased Levels of Abscisic Acid)

Abstract: Previous work showed that the concentration of proline (Pro) increases greatly in the primary root tip of maize (Zea mays 1.) at low water potentials (qw). It was also shown that the maintenance of root elongation at low $ , depends on increased levels of abscisic acid (ABA). In this study we have assessed whether ABA is required for the increase in Pro concentration. Seedlings were grown in vermiculite of various $ , , and endogenous ABA levels were decreased using either fluridone (FLU) or the vp5 mutant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 30 publications
(63 reference statements)
3
77
0
2
Order By: Relevance
“…This increase in activity was suppressed when ABA accumulation and elongation were inhibited by treatment with FLU and could be restored with exogenous ABA. It has also been demonstrated that the accumulation of ABA in the primary root at low i// w is required both for the dramatic increase in Pro concentration that occurs in the apical region (Voetberg and Sharp, 1991;Ober and Sharp, 1994) and for restriction of ethylene synthesis and/or sensitivity . Both effects probably involve control at the level of gene regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in activity was suppressed when ABA accumulation and elongation were inhibited by treatment with FLU and could be restored with exogenous ABA. It has also been demonstrated that the accumulation of ABA in the primary root at low i// w is required both for the dramatic increase in Pro concentration that occurs in the apical region (Voetberg and Sharp, 1991;Ober and Sharp, 1994) and for restriction of ethylene synthesis and/or sensitivity . Both effects probably involve control at the level of gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Vermiculite Ilr, values were measured for each experiment by isopiestic thermocouple psychrometry (Boyer and Knipling, 1965). For the FLU treatments, FLU was added at a concentration of 10 p~ to the water mixed with the vermiculite at the time of planting and transplanting (Saab et al, 1990;Ober and Sharp, 1994). Seedlings were then grown in the dark at 29°C and near-saturation humidity.…”
Section: Seedling Culture and Treatmentsmentioning
confidence: 99%
“…Earlier studies showed that proline accumulated as a response to a decrease in water potentials (Handa et al, 1986;Ober & Sharp, 1994;Bussis & Heineke, 1998) and or RWC (Rajagopal et al, 1977;Argandona & Pahlich, 1991). This response in proline content caused some osmotic adjustment (Handa et aI., 1986;Bussis & Heineke, 1998), which enabled the plant to re-acquire turgidity under water shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Proline content has been reported to increase in response to a decrease in water potential (Handa et al, 1986;Ober & Sharp, 1994;Bussis & Heineke, 1998) or RWC (Rajagopal, Balasubramanian & Sinha, 1977;Argandona & Pahlich, 1991). Proline accumulation affects osmotic potential (Bussis & Heineke, 1998) and is therefore regarded as an important criterion for selecting drought tolerant crops (Singh, Aspinall & Paleg, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of genes for ion pumps have become available thus opening the door for their genetic ~nallipulatio~~ in plants (Jia et al, 1992;Bohnert et al, 1995). An alte~~late aplxoach to tolerallce of both high salt and osmotic stress is the accumulation of o~ganic oslnolytes and other nretabolites, such as glycerol, arabitol, mannitol, sugars, proline, glyci~ie-betaine, and probably polyamines (Rliodes and Hanson, 1993;Ober and Sharp, 1994;Chiang ant1 Dandekar, 1995;Ye et al, 1997). The biosynthetic pathways for these protlucts have been elucidated, providing a great potential for plant improve~l~ent through genetic engineering (Bartels and Nelson, 1994;lngram ant1 Bartels, 1996).…”
Section: Tolerance Fo Abiotic Str-essesmentioning
confidence: 99%